Fabrication of Dye-Sensitized Solar Cells (DSSC) Using Mg-Doped ZnO as Photoanode and Extract of Rose Myrtle (Rhodomyrtus tomentosa) as Natural Dye - Nurdin Siregar; Motlan; Jonny Haratua Panggabean; Makmur Sirait; Juniastel Rajagukguk; Noto Susanto Gultom; Fedlu Kedir Sabir (International Journal of Photoenergy)
A dye-sensitized solar cell (DSSC) device using Mg-doped Zn thin films as photoanode and fruit extract of rose myrtle (Rhodomyrtus tomentosa) as the natural dye was investigated. The effect of annealing temperature (400-550°C) on the films of photoanode was systematically studied using an X-ray diffractometer (XRD), UV-Visible Near Infrared (UV-Vis NIR) Spectrophotometer, scanning electron microscopy (SEM), and energy dispersive spectroscopy (EDS). XRD confirm that all sample has the wurtzite hexagonal with crystallite size of 25 nm. The SEM images reveal particles on the surface of the Mg-doped ZnO thin film of irregular shapes. Increasing the annealing temperature leads to a larger particle size and slightly increases bandgap energy. The dye sensitizer of extracted rose myrtle (Rhodomyrtus tomentosa) has a strong absorption at the visible light region. The maximum efficiency of the DSSC device is 3.53% with Mg-ZnO photoanode annealed at 500°C.